2013
DOI: 10.1302/0301-620x.95b2.30450
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of noise generation arising from the large-diameter Delta Motion ceramic total hip bearing

Abstract: Noise generation has been reported with ceramic-on-ceramic articulations in total hip replacement (THR). This study evaluated 208 consecutive Delta Motion THRs at a mean follow-up of 21 months (12 to 35). There were 141 women and 67 men with a mean age of 59 years (22 to 84). Patients were reviewed clinically and radiologically, and the incidence of noise was determined using a newly described assessment method. Noise production was examined against range of movement, ligamentous laxity, patient-reported outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 29 publications
0
91
1
2
Order By: Relevance
“…Although these material improvements would be expected to decrease clinical concerns associated with previous-generation alumina bearings such as ceramic fracture and squeaking, little is known about this new bearing material and intermediateterm effects are unclear [7,15,27]. Therefore, we evaluated complications associated with the use of ceramic-on- ceramic AMC bearings and clinical outcomes including HHS and survivorship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these material improvements would be expected to decrease clinical concerns associated with previous-generation alumina bearings such as ceramic fracture and squeaking, little is known about this new bearing material and intermediateterm effects are unclear [7,15,27]. Therefore, we evaluated complications associated with the use of ceramic-on- ceramic AMC bearings and clinical outcomes including HHS and survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, these material improvements would be expected to decrease mentioned concerns associated with previousgeneration alumina bearings. However, few short-term clinical results have been published [7,15,27] and several questions remain regarding longer term clinical outcomes after THAs using Delta ceramic bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Stanat and Capozzi [30], in a metaanalysis of 12 studies assessing outcomes after CoC THA, noted the frequency of squeaking to be 2.4%. However, studies assessing noise generation as a whole (inclusive of squeaking) have reported much higher frequency rates [23,24]. In a prospective evaluation of 208 CoC THAs, McDonnell et al [24] noted 11% to report noises other than squeaking, 8% irreproducible squeaking, and 13% reproducible squeaking.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies assessing noise generation as a whole (inclusive of squeaking) have reported much higher frequency rates [23,24]. In a prospective evaluation of 208 CoC THAs, McDonnell et al [24] noted 11% to report noises other than squeaking, 8% irreproducible squeaking, and 13% reproducible squeaking. Thus, only 69% of patients were noted to have ''silent'' hips in this series of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation